The long-term consequences of the global 1918 influenza pandemic: A systematic analysis of census data from 51 countries - Juditha Wójcik; Christian Bommer; Dominik Naeher; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2022)
Several country-level studies have identified long-term adverse effects of in-utero exposure to the 1918 influenza pandemic (also known as the Spanish Flu) on economic outcomes. In-utero conditions are theoretically linked to adult health and socio-economic status through the fetal origins hypothesis. Historical exposure to the Spanish Flu provides a natural experiment to test this hypothesis. Although the Spanish Flu was a global phenomenon, with an estimated 500 million people infected worldwide, no comprehensive global study on its long-term economic effects exists. We address this gap by systematically analyzing harmonized census data from 51 countries. Using the same empirical approach as previous studies, we find no evidence of consistent long-term effects on educational attainment and employment. Overall, our results are difficult to reconcile with the view that in-utero exposure to the 1918 influenza pandemic was associated with important long-term adverse effects on economic outcomes at the population level. A comprehensive set of robustness checks do not alter this conclusion.
Keywords: I15; N30; O57; 330; Spanish Flu; 1918 Influenza Pandemic; Fetal Origins Hypothesis